2013
DOI: 10.1016/j.ygcen.2012.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Androgen feedback effects on LH and FSH, and photoperiodic control of reproduction in male three-spined sticklebacks, Gasterosteus aculeatus

Abstract: , M. et al. (2013) "Androgen feedback effects on LH and FSH, and photoperiodic control of reproduction in male three-spined sticklebacks, Gasterosteus aculeatus" General and Comparative Endocrinology, Access to the published version may require subscription. Sexual maturation in the stickleback is controlled by photoperiod. The aim of this study was to find out whether changes in feedback effects exerted by sex steroids could mediate the photoperiodic effect, which is regarded to be of an all-or-nothing char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
(51 reference statements)
2
9
0
Order By: Relevance
“…Both traits were suppressed by castration and stimulated by 11 KA, also consistent with previous reports [41], [42]. Levels of lws mRNA were higher in sexually mature than in immature male and female sticklebacks.…”
Section: Discussionsupporting
confidence: 92%
“…Both traits were suppressed by castration and stimulated by 11 KA, also consistent with previous reports [41], [42]. Levels of lws mRNA were higher in sexually mature than in immature male and female sticklebacks.…”
Section: Discussionsupporting
confidence: 92%
“…However, expression of both gonadotropic hormones was very low in the period when spermatogenesis commenced in June. The seasonal pattern of gonadotropic hormones may be induced by photoperiodic changes, because male sticklebacks have higher levels of mRNA for both LHβ and FSHβ under a long-day condition (16 h light:8 h dark) than those kept under a short-day condition (8 h light:16 h dark) (Shao et al, 2013). The expression of gonadotropins changes not only seasonally but also depending on the nesting cycle of the stickleback.…”
Section: Gonadotropinsmentioning
confidence: 99%
“…Recent genetic and genomic studies have revealed the molecular mechanisms underlying the morphological, physiological and behavioural divergence between anadromous and freshwater populations of three-spined stickleback (Chan et al, 2010;Greenwood et al, 2013;Indjeian et al, 2016;Marques et al, 2017;Miller et al, 2007;O'Brown et al, 2015;Xie et al, 2019). Third, as discussed in detail below, the endocrine mechanisms underlying seasonal reproduction have been investigated in the three-spined stickleback (Hellqvist et al, 2006;Shao et al, 2013Shao et al, , 2015Sokołowska et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A number of genomic regions underlying morphological changes have been identified with promising candidate genes, but these candidates have not yet been functionally tested 912 . In addition, sticklebacks are common models for studies of population genetics/genomics 13,14 , speciation 15 , behavior 1 , endocrinology 16 , ecotoxicology 17 , immunology 18 and parasitology 19 . Future studies in each of these fields will benefit from the ability to perform functional genetic manipulations in sticklebacks.…”
Section: Introductionmentioning
confidence: 99%